ENVIRONMENTAL EDUCATION AND ENVIRONMENTAL AWARENESS OF YOUNG PEOPLE - Murodova Khilola Umarkulovna (PEDAGOGS, 2025)
Abstract. Environmental education and environmental awareness of young people is one of the important socio-cultural processes that serves the sustainable development of society. This process is aimed at forming harmonious relationships between man and nature, developing skills in understanding environmental problems and finding solutions to them. This study discusses the methods, principles of environmental education and its role in improving the environmental culture of the younger generation. Environmental education is a continuous process from preschool institutions to the higher education system, which includes not only providing theoretical knowledge, but also the formation of practical skills. The role of family education, the media and various non-governmental organizations in the formation of environmental awareness is also emphasized. The study also covers modern environmental problems, climate change, environmental pollution and their impact on human life. At the same time, the effectiveness of interactive educational methods, ecological events and projects, and ecological propaganda on social networks to increase the ecological responsibility of young people was studied. This work highlights the importance of ecological education on a scientific basis and draws attention to the urgent issues of educating young people to be environmentally conscious.